Agrarian Institutions and Intersectoral Linkages in India: Implications for the Economic Well-Being of Agricultural Households - SAHIL MEHRA (Asian Development Review)
The Indian economy has been experiencing high rates of growth in recent decades, primarily led by the industrial and service sectors, particularly between 2003 and 2012. However, the agriculture sector has been suffering economic distress despite experiencing increased intersectoral linkages with the rapidly growing nonagriculture sectors. It is argued that increasing linkages on their own may not be a sufficient condition for improving the economic well-being of agricultural households unless these linkages are combined with access to appropriate institutions specific to the agriculture sector—such as access to output markets, formal credit, and technical sources of information—that can generate positive spillovers. Using farm-household-level disaggregated data provided by the Situation Assessment Surveys for 2003 and 2013, I investigate the complementary relationship between intersectoral linkages and access to agrarian institutions in facilitating improvements in household agricultural income. I find that the magnitude of the linkage effect is higher for households that have access to various agrarian institutions compared with those that do not.